BENTUK PEMBERDAYAAN DAN MANFAAT ‘TOURISM AND HOME ASSISTANT PROGRAM’ TERHADAP PARIWISATA DI KABUPATEN BULELENG - I Gede Sukma Adisatria Sukadana; Ni Made Sofia Wijaya; Dewa Putu Oka Prasiasa (JURNAL MASTER PARIWISATA, 2017)
The aim of this study is to analyze the forms of empowerment carried at Tourism and Home Assistant Program, its model of empowerment, and its advantage on tourism activity in Buleleng Regency. The problems of the study were conducted with qualitative phenomenology approach. Data of the study were analyzed by utilizing qualitative descriptive method. Data collection techniques utilized observation, documentation studies, and in-depth interviews. The results of this study shows that the forms of community development activities in Tourism and Home Assistant Program were one year tourism training and providing incidental help. Analysis of empowerment model Tourism and Home Assistant Program consisted of creating relevant curriculum, management, marketing, supervision, implementation of clear education system, recruitment systems, cooperation with the users of the graduates, and provide sustained professional development. The interpretation of the data indicates that Tourism and Home Assistant Training Program has advantage on tourism activity of Buleleng Regency such as promotion of tourism activity through social care activities.